EDUKASI PEMILAHAN SAMPAH UNTUK MENINGKATKAN PENGETAHUAN SISWA MADRASAH IBTIDAIYAH DI KOTA SUNGAI PENUH - Tiara, Tiara; Adelia, Ismi (Institut Agama Islam Negeri Kerinci, 2025)
Trash is a critical issue that requires serious attention. Education about waste management has become one of the essential pillars in improving public knowledge and participation in addressing waste problems. This activity aims to educate students about waste to enhance their understanding. The activity was carried out through interactive workshops divided into several stages: pretest, lecture and demonstration, question and answer session, simulation, and posttest. The participants in this activity were fourth-grade students from MIS 08/E72 Debai, Kota Sungai Penuh. The results of the activity showed an improvement in students' knowledge about waste, as indicated by an average post-test score of 80.00 compared to a pre-test score of 28.33. The students appeared enthusiastic and motivated during this educational activity, as evidenced by their active participation in the question-and-answer sessions.